2019
DOI: 10.1021/acs.jctc.8b01290
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Activity Cliffs with Free-Energy Perturbation

Abstract: Activity cliffs (ACs) are an important type of structure−activity relationship in medicinal chemistry where small structural changes result in unexpectedly large differences in biological activity. Being able to predict these changes would have a profound impact on lead optimization of drug candidates. Free-energy perturbation is an ideal tool for predicting relative binding energy differences for small structural modifications, but its performance for ACs is unknown. Here, we show that FEP can on average pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 68 publications
(91 reference statements)
1
84
0
Order By: Relevance
“…This may or may not be valid, depending on each and every case under study; when invalid, however, its predictions will fail badly. Thus, for example, when the free energy changes more or less discontinuously with molecular structure, as it does for the case of free energy cliffs [94], there is no way such an ML algorithm will in general be able to spot such phenomena. It could only do so if the coverage of the state space were exceptionally dense, implying that the data upon which it has been trained would need to be enormous.…”
Section: Methods For Free Energy Calculationmentioning
confidence: 99%
“…This may or may not be valid, depending on each and every case under study; when invalid, however, its predictions will fail badly. Thus, for example, when the free energy changes more or less discontinuously with molecular structure, as it does for the case of free energy cliffs [94], there is no way such an ML algorithm will in general be able to spot such phenomena. It could only do so if the coverage of the state space were exceptionally dense, implying that the data upon which it has been trained would need to be enormous.…”
Section: Methods For Free Energy Calculationmentioning
confidence: 99%
“…In turn, application of FEP to a vast range of protein-ligand systems revealed that the method can indeed deliver accurate relative binding affinity predictions with an error of <1 kcal mol À1 with respect to experiment. [23][24][25][26][27][28][29][30][31][32][33][34][35][36] However, the application of FEP using most MD soware remains challenging, preventing its widescale uptake.…”
Section: Introductionmentioning
confidence: 99%
“…For comparison, it has been reported that FEP+ takes 86 minutes to sample a 1ns perturbation for 12 windows on 4 NVIDIA Tesla K80 for BACE1 69 complexes (containing 401 amino acids) and 34 minutes for the corresponding simulations of the solvated ligands. 70 This corresponds to ~29 min/ns for the complex and ~11 min/ns for the ligand-only simulations, respectively. The Gromacs-FEP implementation was reported to be 3 to 6 times slower than FEP+.…”
Section: Computational Costmentioning
confidence: 98%
“…However, there is evidence that shorter calculations times (usually 1 ns) may be sufficient to obtain a reasonable free energy estimate for certain classes of perturbations. 23,70 Thus, there may be scope to further…”
Section: Computational Costmentioning
confidence: 99%